Solving task of vessel’s running time and fuel consumption measurement - Кирилычев, Александр Александрович; Ивановский, Николай Владимирович; Голиков, Сергей Павлович; Куценко, Дмитрий Григорьевич; Зеленцов, Виталий Алексеевич (Eastern-European Journal of Enterprise Technologies, 2012)
This article describes an actual problem – rating of running time and fuel consumption. From the economic point of view transportation will be more favorable if such important factors as cost of fuel, its availability in ports of call and cost of a freight of a vessel are taken into account. Calculation of these tasks can be carried out only on the basis of certain criteria, for example, a minimum of fuel consumption, a maximum of profit, etc. Therefore, special economic patterns should be developed in connection with rating of running time. Such construction will help us to avoid common errors. Shortcomings of existing techniques for the solution of this task have been revealed, namely: great affect of thehuman factor and severe simplification of mathematical patterns. As a result solutions for this task are offered. In order to create the syetm of rating meeting practical requirements it is necessary to have available: - a multiple-factor method of vessel’s speed calculation and fuel consumption for the main and auxilairy engines associated with it ; - an economic pattern in order to determine vessels’ traffic mode